KERJASAMA POLRI DAN IOM DALAM MENANGGULANGI PERDAGANGAN MANUSIA DI INDONESIA TAHUN 2007-2013 - Darmastuti, Riska Ruly; Susitianingsih, Hermini; Pattipeilohy, Shary Charlotte (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2015)
For several years, Indonesia has become the source, transit, anddestination country for human trafficking. According to IOM,Indonesia is South-East Asia’s second largest country for humantrafficking case after Thailand. To fight human trafficking inIndonesia, INP, as part of law enforcement body in Indonesia, hascooperated with IOM and givenspecial attention to this issue. Thisresearch aims to analyse thesupporting andobstructing factors to suchcooperation, considering the fluctuative number of human traffickingcase in Indonesia between 2007-2013. This research employs theoryof transnational crime, human rights, and liberal institusionalism todescribtively analysedata collected through interview as well as otherrelated literatures. The result shows that there are obstructing factorssuch as coordination, internal problem of INP, and time management,which hinder this cooperation from achieving its optimum outcome.